The selection of sago flour suppliers using Multi Criteria Group Decision Making approach with different sets of criteria - Usamah Afiq Nuruddin; Indah Pratiwi; Afiqoh Akmalia Fahmi; Eko Setiawan (AGROINTEK, 2026)
Tiga Hati Mutiara, a producer of pearl sago, has only one supplier of raw material for sago flour for the production of sago pearls. Based on data from the Indonesian Ministry of Agriculture, there are 13 sago-producing provinces. These 13 sago-producing provinces can become alternative sago suppliers for Tiga Hati Mutiara. The purpose of this research is to find the best supplier of sago flour for Tiga Hati Mutiara, in accordance with its needs and goals. To address the problem under concern, this research uses the MCGDM approach with a different set of criteria. This method requires expert data, such as decision makers, supplier alternatives, and supplier criteria. The study found that supplier alternative 2, namely Terong Mas, was chosen as the main supplier of sago flour out of six supplier alternatives and fifteen sub-criteria used. This research is expected to be a suggestion for improvement in supplier selection decision-making for the company, as well as material for further research literacy.